Representation of Islamic Culture in the Islamic Documentary Empire of Faith: A Semiotic Analysis of Roland Barthes - FUADI, Muhamad Hanif; WAFA, Ah. Khairul; KUSWANTO, Ade Arena; RAMADHANITA, Frista Fitriany (Journal of Social Sciences and Cultural Study, 2025)
This article analyzes the representation of Islamic culture in the documentary film Islam: Empire of Faith using Roland Barthes' semiotic approach. The film provides a historical overview of Islamic civilization, from its birth to its heyday, including its contributions to art, architecture, science, and politics. By applying Barthes' concepts of denotation, connotation, and myth, this study reveals how visual and narrative signs in the film construct the representation of Islamic culture in the eyes of the audience. This analysis shows that the film constructs an idealistic narrative about the splendor and glory of Islamic civilization but also carries an ideological bias that reinforces Western myths about the Islamic world, such as the image of Islam as backward and exclusive. This research is important to understand how the media shapes cultural images and religious identities and its implications for intercultural understanding. Using Barthes' semiotic approach, this study reveals how the media constructs myths that can influence the audience's perspective on Islamic culture, reinforce stereotypes, or even pave the way for more complex understandings. On the one hand, this film has the potential to introduce the beauty and richness of Islamic history. However, on the other hand, it also reflects certain ways of presenting narratives that could worsen or strengthen the distortion in the relationship between the West and Islam.